Ultrahigh Carrier Mobility in Cd3As2 Nanowires. Issue 2 (3rd November 2022) - Singh, Angadjit; Schoenherr, Piet; Barnes, Crispin; Hesjedal, Thorsten
Abstract : Magnetotransport measurements are carried out on nanowires of the Dirac semimetal Cd 3 As 2 . Weak antilocalization is observed at 1.9 K, consistent with the presence of strong spin–orbit interaction. With decreasing temperature, Shubnikov–de Haas oscillations are seen, revealing an ultrahigh mobility of ≈ 57 000 cm 2 V − 1 s − 1 at 1.9 K. The strong oscillations display a linear dependence of the Landau‐level index on the inverse of the magnetic field, yielding an intercept that is consistent with a π Berry phase—the signature feature of Dirac fermions. By studying the fundamental properties of Dirac materials, new avenues can be explored by exploiting their unique properties for spintronics and magnetoelectronic devices. Abstract : Cadmium arsenide ( Cd 3 As 2 ) is a topological Dirac semimetal with intriguing electronic properties. In Cd 3 As 2 nanowires, which crystallize in the noncentrosymmetric space group I 4 1 c d, helicity‐dependent THz emission is discovered. Here, Singh et al. present magnetotransport measurements of these nanowires, reporting an ultrahigh mobility and a Berry phase of π consistent with the existence of 3D Dirac fermions.